Analysis of the Influence of School for Great Women (Sekolah Perempuan Hebat) Model on Family Resilience in Dano Village Indonesia - Bambang Rustanto; Marwanti, Theresia Martina; Kartika, Tuti Kartika; Ariska , Dela Vinka (Asean Social Work Journal, 2025)
The government's efforts to protect and empower women are realized through the School for Great Women model. The problem of the study is how the School for Great Women Model influence family resilience in Dano Indonesia Village. The research method used is a mixed method with an explanatory partial design type. There are one hundred women members of the School for Great Women in Dano Village. The result of this study is that there is a difference in the average pre-test and post-test scores in participating in the School for Great Women model. This shows that the School for Great Women model in Dano Indonesia Village can improve family resilience. The aspect of physical resilience, namely increased physical skills in meeting daily needs such as sewing, cooking, food processing, and gardening by utilizing land or home yards. Changes in the aspect of social resilience are the increased ability to relate and communicate with both husband and children, so that relationships in the family become more harmonious and equal. Relationships with children have become better by no longer yelling at children. Then, changes in the aspect of psychological resilience are the increased ability to manage stress and solve problems together.